A REVIEW OF BUDGETARY SLACK FROM THE CORPORATE GOVERNANCE PERSPECTIVES - Jia Bin; Noorul Azwin Md Nasir; Zaminor Zamzamir@Zamzamin; Amira Jamil, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
Existing research and practice have found that budget management does not work as expected, and some problems incompatible with firm development are gradually exposed, budgetary slack being one of them. Using the research method of literature review, this paper identifies the determinants of budgetary slack from the perspective of corporate governance as: executive remuneration, executive risk appetite, independent directors and director expertise, respectively, which fills the gap between the influence of executive characteristics and board characteristics on budgetary slack. Studying the determinants of budgetary slack can help firms improve the quality of budget management, optimise internal control and enhance the quality of corporate governance.